Facilitating reflection, confidence, and positive mirror effect in teacher practicum: a serial multiple mediation model - Wing W. Y. Ho; Yan H. Y. Lau; Eric K. L. Li (Humanities & Social Sciences Communications)
Abstract This study investigates the mediating role of reflective thinking practice in the relationship between practicum and positive mirror effect in early childhood special education teacher training. The study participants comprise students enrolled in undergraduate early childhood teacher education programs specific to special education. This study entails a post-evaluation using the Experiential Learning Experiences Scale, Reflective Practice Questionnaire, and Mirror Effects Inventory to assess practicum experiences, reflective thinking practices, and mirror effects via an online survey after engaging in experiential learning, particularly a teaching practicum. The hypothetical serial multiple mediation model is analyzed using PROCESS macro. The results reveal that the relationship between practicum experiences and the positive mirror effect was at least partially explained by the desire for improvement, reflective capacity, and confidence. However, the desire for improvement is not sufficient to demonstrate a mediation effect. Moreover, the findings suggest that reflective capacity fostering student teachers’ confidence may generate a positive mirror effect. These findings highlight the beneficial effects of reflective capacity in the relationship between practicum experiences and positive mirror effects in early childhood special education teacher training. This implies that practicum experiences can contribute positively to reflective capacity and foster student teachers’ affective learning experiences, ultimately enhancing the overall professionalism of early childhood special education. This study provides essential insights indicating that further research should focus on extracting practical knowledge and reflective experiences in special education from pre-service and experienced in-service teachers, along with methods to cultivate positive affective experience and confidence, thereby generating a positive mirror effect in practicums across diverse disciplines.